2016
DOI: 10.1007/s00125-016-3916-5
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 receptor EP3 inhibits water reabsorption and contributes to polyuria and kidney injury in a streptozotocin-induced mouse model of diabetes

Abstract: Aims/hypothesis The first clinical manifestation of diabetes is polyuria. The prostaglandin E 2 (PGE 2 ) receptor EP 3 antagonises arginine vasopressin (AVP)-mediated water reabsorption and its expression is increased in the diabetic kidney. The purpose of this work was to study the contribution of EP 3 to diabetic polyuria and renal injury. -STZ mice also had increased protein expression of aquaporin-1, aquaporin-2, and urea transporter A1, and reduced urinary AVP excretion, but increased medullary V2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
(98 reference statements)
3
29
0
Order By: Relevance
“…12,13 Inner medullary CD display blunted AVP-water flux but enhanced urea permeability in response to PGE2. 14,15 We have recently demonstrated a role for PGE2/EP1 in PT water transport, 16 and confirmed that a disturbance in EP3 function only partially contributes to defective urine-concentrating ability in diabetic mice, 17 highlighting a possible involvement of EP1 in kidney concentrating function. Accumulating evidence suggests that a sustained activation of the local RAS within the CD has a key role in the development of angiotensin-II-dependent hypertension.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…12,13 Inner medullary CD display blunted AVP-water flux but enhanced urea permeability in response to PGE2. 14,15 We have recently demonstrated a role for PGE2/EP1 in PT water transport, 16 and confirmed that a disturbance in EP3 function only partially contributes to defective urine-concentrating ability in diabetic mice, 17 highlighting a possible involvement of EP1 in kidney concentrating function. Accumulating evidence suggests that a sustained activation of the local RAS within the CD has a key role in the development of angiotensin-II-dependent hypertension.…”
mentioning
confidence: 58%
“…This is interesting considering that we showed that COX1 and COX2 were unchanged in EP3 − / − . 17 Though not much is known about the signals that trigger COX2 downregulation, Haddad et al 30 demonstrated that EP1 may promote COX2 ubiquitination and subsequent degradation. In the medulla, the data suggest that both COX1 and COX2 are downregulated by PGE2/EP1, but not as simple to interpret at this time, considering that Htn mice also display similar changes as HtnEP1 − / − with respect to COX1 mRNA expression, yet EP1 mRNA levels are significantly elevated in Htn medulla.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the most widely produced prostanoid in the human body . PGE2 plays important roles in various pathological and physiological functions, such as cell proliferation, apoptosis, cancer, inflammation, hypertension, Alzeheimer's disease, diabetes and immune response . PGE2 functions through activation of four specific G‐protein‐coupled receptors (GPCR) subtypes, termed EP1, EP2, EP3 and EP4 .…”
Section: Introductionmentioning
confidence: 99%